Pemanfaatan Media G Develop Untuk Membuat Game Edukasi Di SMA Negeri 1 Pekanbaru - Muhammad Zidhan; Finanta Okmayura; Ahmad Khaidir (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of G Develop in the context of education is still limited. Some of the obstacles that may be faced in utilizing G Develop to create educational games at SMA Negeri 1 Pekanbaru include, Teachers do not have sufficient knowledge and skills in using G Develop as learning media. This research will use a qualitative approach with a case study research design. This approach was chosen to gain an in-depth understanding of the process of creating educational games using G Develop and its impact on learning at SMA Negeri 1 Pekanbaru. Educational games have been successfully developed using G Develop in accordance with the applicable curriculum at SMA Negeri 1 Pekanbaru. This game is designed to strengthen the understanding of certain subject concepts and increase students' interest and motivation to learn. The final evaluation shows that the educational game has successfully achieved the learning objectives set. Students showed high interest and motivation in using this game as an additional learning tool. It is recommended to develop more educational games that cover various subjects taught at SMA Negeri 1 Pekanbaru. This will allow more students to access learning materials through an engaging approach. Teachers need to be given further training in the use of G Develop and the integration of educational games into the learning process.